2021
DOI: 10.1021/acs.jpcc.1c06355
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Structure–Performance Correlation of TiC MXenes as Cathode Catalysts for Li-O2 Batteries

Abstract: Two-dimensional TiC MXenes have high stability and large specific surface area, as well as show great application prospect as cathode catalysts for Li-O 2 batteries. There are at least three different structures of TiC MXenes labeled as Ti 2 C, Ti 3 C 2 , and Ti 4 C 3 MXenes. Understanding the effect of structure on the catalytic activity of TiC MXenes is of great significance for the rational design of catalyst. In this study, the adsorption structures of H, O, F, and OH functional groups upon TiC MXenes unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Since the first MXene (2D Ti 3 C 2 ) was reported in 2011, more than 30 MXenes have been experimentally synthesized and over 100 theoretically predicted . The electronic structures of MXenes vary widely from metallic to insulating, and MXenes have been used to produce materials with properties relevant to a variety of applications such as energy storage, transparent conductors and heaters, photo-thermal therapy, photocatalysts, thermoelectrics, superconductors, , ferromagnets, , and topological insulators. …”
Section: Introductionmentioning
confidence: 99%
“…Since the first MXene (2D Ti 3 C 2 ) was reported in 2011, more than 30 MXenes have been experimentally synthesized and over 100 theoretically predicted . The electronic structures of MXenes vary widely from metallic to insulating, and MXenes have been used to produce materials with properties relevant to a variety of applications such as energy storage, transparent conductors and heaters, photo-thermal therapy, photocatalysts, thermoelectrics, superconductors, , ferromagnets, , and topological insulators. …”
Section: Introductionmentioning
confidence: 99%
“…According to the experimental calculations, the estimated theoretical energy storage densities of Ti 4 C 3 O, Ti 3 C 2 O 2 , and Ti 2 CO 2 are 0.562, 0.476, and 0.372 kWh kg –1 , respectively, on the basis of the assumption that their SSA is ≈100 m 2 g –1 . , The study also shows that discharge potential for bare TiC MXene (Ti 3 C 2 ) was about 3.21 and 9.36 for ORR and OER, respectively, while for TiC MXene with O terminations (Ti 3 C 2 O 2 ), it reduced significantly, i.e., 0.18 V for ORR and 0.22 V for OER, concluding that oxygen terminations in TiC MXene have a stronger adsorption capacity to promote catalytic activity and, in turn, reduce the overpotential. , …”
Section: Applications In Electrochemical Energy Storage Devicesmentioning
confidence: 80%
“…65,129 The study also shows that discharge potential for bare TiC MXene (Ti 3 C 2 ) was about 3.21 and 9.36 for ORR and OER, respectively, while for TiC MXene with O terminations (Ti 3 C 2 O 2 ), it reduced significantly, i.e., 0.18 V for ORR and 0.22 V for OER, concluding that oxygen terminations in TiC MXene have a stronger adsorption capacity to promote catalytic activity and, in turn, reduce the overpotential. 48,130 TiC MXenes with different surface terminations effected electrode potential differently, while TiC MXenes with Oterminations had the fastest electronic transmission due to its high electron energy and they form transition metal oxides-like surfaces, which are active for redox reactions. 126,131 It was also revealed that TiC MXenes with O-terminations can provide additional catalytic sites for the formation as well as the decomposition of the deposited Li 2 O 2 and can facilitate growth on the Li 2 O 2 surface.…”
Section: Comparison Of Mxenes and Other Cathode Materialsmentioning
confidence: 99%
See 2 more Smart Citations